Commercialization secrets for scientists and engineers - Szycher, Michael (CRC Press, Taylor & Francis Group, 2017)
Commercializing a knowledge-based product or service requires a realistic, methodical approach combined with a great deal of perseverance. Commercialization Secrets for Scientists and Engineersserves as a high-level guide to answering key questions and critical issues that confront founding entrepreneurs on their quest to commercialize their knowledge-based innovations. It highlights the unique problems shared by all technologists across knowledge-intensive fields and how to overcome the most predictable obstacles faced by technology entrepreneurs. It demystifies the process of commercializing advanced products that require a high degree of specialized knowledge. Typically, these are "disruptive technologies" with the potential to revolutionize whole industries. The book simplifies the launch of high-tech ventures such as pharmaceuticals, genetic and biotechnology products, wireless devices, fuel cells, and minimally invasive medical devices. Additionally, it will help readers bring their disruptive technologies to profitability.